Production of biodiesel (isopropyl ester) from coconut oil by microwave assisted transesterification: parametric study and optimization - Rachmaditasari, Rheinanda; Darojat, Muhamad Irfaid; Mahfud, Mahfud (International Journal of Renewable Energy Development, 2024)
Biodiesel, a renewable fuel for diesel vehicle engines, has been commonly produced from transesterification process involving triglycerides from vegetable oil with alcohol. One of the most promising candidates for vegetable oil due to its abundance in Indonesia is coconut oil. However, the short carbon chain present in coconut oil necessitates the use of longer-chain alcohol types to adjust to the biodiesel carbon chain, such as isopropanol. Therefore, this research focused on producing biodiesel (isopropyl ester) from coconut oil using isopropanol and NaOH catalyst through a transesterification process. To enhance this process, microwave technology was utilized for its ability to lower the biodiesel production reaction time from the conventional one-hour timeframe to less than ten minutes, increase energy efficiency, and improve biodiesel quality. The primary objective was to investigate the impact of reaction time, catalyst concentration, and microwave power on the isopropyl ester yield. Further optimization was conducted using Response Surface Methodology (RSM) with Box-Behnken Design (BBD) to illustrate the model's effectiveness and applicability. Based on BBD optimization simulation, the optimal condition for producing isopropyl ester from coconut oil using microwave technology is a 1-minute reaction time, 0.2 wt.% NaOH catalyst concentration, and 443.9 W microwave power, maximizing the yield to 99.89%. This research highlights the potential of microwave assisted transesterification and the reliability of this innovative approach, contributing to the development of isopropyl ester production with enhanced quality that meets the specifications of the Indonesian National Standard (SNI).